STRATEGI MENINGKATKAN KINERJA WEB UNIVERSITAS MUHAMMADIYAH SEMARANG MENUJU PERINGKAT WEBOMETRICS - Bambang Supradono (MEDIA ELEKTRIKA, 2010)
Nowadays many University competing improve the performance of the network that they have to list in the Webometrics ranking. Semarang Muhammadiyah University (UNIMUS) is actually a University relatively new also trying to enter competition Webometrics ranking of world universities. This study aims to fill the framework of a strategy to achieve the webometria range. The methodology used for the first time to evaluate the performance of the website parameters unimus webometricos and then create a reference point of three national universities that has entered the ranks of the highest ranking of Webometrics, medium and minor at the national level. Later followed by the analysis of webometria evaluation indicators include the size, visibitity, erudite and rich text files. The results were compiled from then action plans in order to set gap of 3 universities in reference. Thus, the benefits can provide guidance for UNIMUS into the Webometrics rangkings. Keywords : UNIMUUS, Webometric